AB0649 Use of biological dmards in patients with primary vasculitis; results from turkbio registry. (12th June 2018) - Yazici, A.; Cefle, A.; Dalkilic, E.; Pehlivan, Y.; Can, G.; Goker, B.; Tufan, A.; Senel, S.; Koca, S.S.; Akar, S.; Akkoç, N.; Onen, F.
Abstract : Background: Untreated, The systemic vasculitides can be devastating, with high rates of morbidity and mortality. Recently, most of biological agents have evaluated in clinical trials, and management of systemic vasculitis has been revolutionised over the last decade. 1 2 Objectives: Here, we report the frequency of using and switching rate of biological agents in different types of primary vasculitis patients. Methods: TURKBIO registry is the Turkish version of Danish DANBIO rheumatological database which has been established in 2011. All patients with primary vasculitis who received biological agents registered in TURKBIO registry between dates of October 2011 and January 2018 were included in this study. The demographic data, the date of starting to use of biological drug, frequency of using and switching biological agents were collected. Results: As of January 2018, 108 primary vasculitis patients were recruited (mean age: 38.4±10.9 [min-max: 19–67]; female 48%); 48 patients (44%) of them had Behcet's disease (BH), 35 (32%) had Takayasu arteritis (TA), 24 (22%) had granulomatosis polyangiitis, and one of them had microscopic polyangiitis. The most commonly used biological agents in current treatment were as follows: 75% of patients received infliximab (INF) and 15% received adalimumab (ADA) in BD patients; 48.6% received tocilizumab (TCZ), 23% received INF and 20% received ADA in TA patients; all patients with granulomatosis with polyangiitis (GPA) were treated with rituximab. The switching rate was 54% in TA patients, 27% in BD patients, and 4% in GPA patients. The most frequent switching was found at INF (28/78) and ADA (9/23) which was the most commonly used agent in TA and BD. The lowest switching rate was TCZ (2/17) in TA patients (table 1). Conclusions: This is the first evaluation of primary vasculitis patients who used biological agents from TURKBIO registry. According our data, there was high switching rate with anti-TNF agents in TA patients. The limitation of this study was the low number of the patients with primary vasculitis who used biological agents. References: [1] Jarrot PA, Kaplanski G. Anti-TNF-alpha therapy and systemic vasculitis. Mediators Inflamm. 2014;2014:493593. [2] Henderson CF, Seo P. Biologic agents in systemic vasculitis. Int J Clin Rheumtol. 2011; 6(4):453–462. Acknowledgements: None Disclosure of Interest: None declared